Analysis of maternal and obstetric risk factors for retinopathy of prematurity - Isjanovski, Igor; Isjanovski, Viktor (Medical faculty, Ss Cyril and Methodius University in Skopje, 2018)
ABSTRACT Retinopathy of Prematurity (ROP) is a major cause of preventable blindness in preterm infants. The incidence of ROP is increasing in developing countries due to increased survival of preterm infants. Retinopathy of prematurity (ROP) is a serious complication of prematurity and can lead to blindness unless is recognized and treated early The aim of our study was to study maternal and obstetric risk factors for ROP. The research was an analytical "Case control" study in the period 2015-2016.The study included 195 premature babies that meet the criteria of the American Academy of Ophthalmology (AAO), with BW less than 1500 g and gestational age less than 30 GW. Mothers were divided into two groups according the newborns with ROP and without. In order to achieve the goals, a two-part survey questionnaire was used, the first part of the questionnaire refers to questions for the mother. In Vitro Fertilization increases the chance of ROP more than two and a half times OR = 2.7140 (1.2238-6.8620). As independent factors, multiple pregnancies increase the chance of ROP for two and a half times. Preeclampsia acts protective, reduces the chance of occurrence of ROP. The way of delivery, the number of pregnancies, number of births, alcohol consumption, smoking, narcotics, did not present as risk factors. We should pay attention to the definition of risk factors, their complexity, the development and progression of retinopathy prematurnata and its prevention,because they are just one of the issues facing ophthalmologists and neonatologists throughout his work.
Keywords: maternal and obstetric risk; retinopathy of prematurity